NUTRITIONAL STATUS OF PRESCHOOL CHILDREN - Alexopoulos, Christos Georgios (Medicinski časopis, 2013)
Overweight and obesity means excessive accumulation of fat that is due to an imbalance between intake and energy expenditure. The aim of the study was to analyze the nutritional status of two generations of preschool children in a systematic review of enrollment in primary school in Cuprija, diagnosis of children with excessive body weight and obese children, as well as analyzing the relationship between obesity in preschool children and their parents' employment, eating habits of children and the time that children spend in any physical activity and all in order to assess their current health status. The study obuhvaćeno516 child of two generations of pre-school children, 212 of the generation 2002/2003 and 304 child-generation 2003/2004 and their parents, where nutritional status is verified using the percentile values ​​of BMI. The height and weight of children is a measure of trained medical personnel, and data on height, weight and diet and physical activity as children are collected based on questionnaires completed by parents. Research for Children born between 01.03.2002 and 28.02.2004. was conducted on a systematic review of the compulsory primary school, in March 2009 for children born in the period from 01.03.2003. to 29.02.2004, March 2010. Year. Place of study was the Health Children's Health Center in Cuprija. The incidence of obesity in children for enrollment in first grade is 5.04% and the incidence of excessive body weight is 10.08%. With the increase of body weight were 25 girls (9.96%) were obese, while 13 girls (5.18%). In boys with elevated body mass there were 26 boys (9.81%) while the obese were 14 boys (5.28%). The results of this study showed clearly the existence of the problem of excessive weight gain in enrollment of children in first grade.